Gas transport and optical properties of ABA‐type triblock copolymers designed using fluorine‐containing polyimide macroinitiators with methyl methacrylate. Issue 9 (16th January 2013) - Sato, Shuichi; Ichikawa, Masato; Ose, Takamasa; Miyata, Sou; Takahashi, Yoichi; Kanehashi, Shinji; Matsumoto, Hironaga; Nagai, Kazukiyo
Abstract : The 6FDA‐TeMPD/PMMA ABA‐type Triblock copolymer was synthesized by ATRP. This polymer showed high heat resistance, low refractive index, and high gas barrier property. Abstract: 4, 4'‐(Hexafluoroisopropylidene) diphthalic anhydride 2, 3, 5, 6‐tetramethyl‐1, 4‐phenylenediamine (6FDA‐TeMPD) polyimide macroinitiator was synthesized and reacted with poly(methyl methacrylate) (PMMA) to form an ABA‐type triblock copolymer by atom transfer radical polymerization. The effect of the ABA‐type triblock copolymer structure on solid, thermal, optical and gas transport properties was systematically investigated and compared with the physical blend polymer. The blend polymer was cloudy, whereas the triblock copolymer was colorless and transparent. The PMMA component decomposition temperature for the triblock copolymer slightly shifted to higher temperature, while its gas barrier property was higher than the blend polymer. The refractive index and the gas permeability decreased while maintaining the heat resistance by a high nanoscale distribution of both polymer components. The 6FDA‐TeMPD/PMMA ABA‐type triblock copolymer can be described as a polymer material with high heat resistance, high gas barrier property and low refractive index amongst existing polymers. © 2013 Society of Chemical Industry